Relationship between non-performing loans (NPLs) and macroeconomics variables / Faridahtul Hazimah Fazoli - Fazoli, Faridahtul Hazimah (Faculty of Business and Management, 2011)
Non-Performing Loans (NPLs) can be defined as defaulted loan in which banks are unable to form profit. Usually loans falls due if no interest has been paid in 90 days. This will reduce the bank’s profit if customer did not pay the interest. But, there are few ways for customer if they cannot pay the interest, such as reschedule their loans. The purpose of this study is to analyze the relationship between the NPLs with interest rate, inflation rate and unemployment rate. There is an significant and insignificant relationship between interest rate, inflation rate and unemployment rate with NPLs. This research is appertained with commercial banks in Malaysia. Data were collected from secondary data which published by Bank Negara Malaysia from February 2006 - December 2010 in monthly. The technique used is single linear regression method to see the relationship between dependent and independent variables. Non-Performing Loans (NPLs) will be used as dependent variables and interest rate (INT), inflation rate (INF) and unemployment rate (UNP) will be used as independent variables.